2018
DOI: 10.1038/s41598-018-21267-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 delays the early development of scleractinian coral Acropora gemmifera

Abstract: The effects of elevated CO2 on the early life stages of coral were investigated by culturing the pelagic larvae and new recruits of Acropora gemmifera at three concentrations of CO2 (corresponding to pH = 8.1, 7.8 and 7.5, respectively). Acidified seawater resulted in fewer A. gemmifera larvae settling, and led to the production of smaller new recruits by slowing the development of the skeleton. The delayed development of new recruits due to elevated CO2 was consistent with the downregulation of calcification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
(49 reference statements)
0
17
1
Order By: Relevance
“…< 25%). Yuan et al (2018) found reduced settlement in A. gemmifera larvae when exposed to reduced pH NBS (7.8 and 7.5) at the time of settlement. In echinoderms, Dupont et al (2013) noted delayed settlement in S. droebachiensis, while in the sea urchin Paracentrotus lividus, García et al (2015) observed delayed settlement by 8 d in pH NBS 7.7 compared to pH NBS 8.1, and no settlement at pH NBS 7.4.…”
Section: Settlement Processesmentioning
confidence: 82%
See 1 more Smart Citation
“…< 25%). Yuan et al (2018) found reduced settlement in A. gemmifera larvae when exposed to reduced pH NBS (7.8 and 7.5) at the time of settlement. In echinoderms, Dupont et al (2013) noted delayed settlement in S. droebachiensis, while in the sea urchin Paracentrotus lividus, García et al (2015) observed delayed settlement by 8 d in pH NBS 7.7 compared to pH NBS 8.1, and no settlement at pH NBS 7.4.…”
Section: Settlement Processesmentioning
confidence: 82%
“…The juveniles generated in OA conditions were smaller than the controls (Wangensteen et al 2013). In corals, Yuan et al (2018) observed reduced percentage settlement of Acropora gemmifera larvae that had been cultured at 3 concentrations of CO 2 (corresponding to pH NBS 8.1, 7.8 and 7.5). After settlement, the recruits showed decreased calcification and growth, changes consistent with the downregulation of calcification-related genes.…”
Section: Carryover Effectsmentioning
confidence: 85%
“…The copyright holder for this preprint (which this version posted July 20, 2021. ; https://doi.org/10.1101/2021.07.19.452948 doi: bioRxiv preprint OA and Coral Development 4 Yuan et al, 2018). The increased energetic costs of maintaining homeostatic processes under disrupted acid-base balances and ionic gradients can additionally slow development and reduce growth of marine invertebrate larvae and recruits (Albright and Langdon, 2011;Byrne, 2012;Przeslawski et al, 2015;Timmins-Schiffman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research has continued to focus on mollusks, arthropods and echinoderms, however, cnidarian settlement and metamorphosis (Foster et al, 2015;Olsen et al, 2015;Viyakarn et al, 2015;Fabricius et al, 2017;Yuan et al, 2018), the settlement behavior and swimming activity of a bryozoan (Pecquet et al, 2017), and settlement of an annelid (Nelson et al, 2020) have also been studied. In addition to continuing to assess the impact of elevated CO 2 on the range of behaviors previously studied (above), a few new behaviors have also been investigated.…”
Section: Introductionmentioning
confidence: 99%